Sex, Violence, and Drugs Among Latin American and Caribbean Adolescents: Do Engaged Parents Make a Difference? - Inder J. Ruprah; Ricardo Sierra (Inter-American Development Bank (IDB), 2016)
This paper uses data from the Global School-based Student Health Survey to investigate the prevalence of health risk behaviors, in particular substance use, risky sexual behavior, and violence among adolescents in 15 Latin American and Caribbean countries. Using logit regressions and meta-analysis, we find that having parents engaged in raising their children is associated with significantly reduced problem behaviors in adolescents. That said, in the Caribbean the prevalence of health risk behaviors in adolescents is higher and engaged parents is lower than in Latin America, and the correlation between engaged parenting and reduced risk behaviors is generally weaker. Nonetheless, for both subgroups of countries, engaged parents do appear to make a difference.
hdl:11319/7557
Keywords: I12; I18; I20; J13; O54; 330; parenting; health risk behaviors; adolescents; Latin America and the Caribbean